A STUDY OF HUMAN VALUES ​​EMBEDDED IN THE SHRIMAD BHAGAVAD GITA AND YOGA SUTRAS - Pant, Mamta; Kaswan, Rajesh Kumar (International Journal of Research -GRANTHAALAYAH, 2026)
This research paper is a study of the human values ​​embedded in two great texts of Indian philosophy: Patanjali's Yoga Sutras and the Shrimad Bhagavad Gita. In the present times, along with material progress, human values ​​are diminishing. The decline of these values ​​has become a global concern. The main objective of this research paper is to explore how the Yamas and Niyamas described in Patanjali's Yoga Sutras and the Gita reveal the moral foundation of an individual. It examines how the mind can be purified through the Yoga Sutras. Similarly, the principles of 'Nishkama Karma' (selfless action) and 'Sthita Prajna' (a person of steady wisdom) in the Gita inspire balanced behavior in society. While Yoga strengthens inner discipline, the Gita paves the way for equality. The integration of these two should form the basis of the modern education system and character building, leading to a higher and more divine life for the individual.